2019
DOI: 10.3390/foods8020068
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Bioactivity of Coffee Silverskin Melanoidins

Abstract: Melanoidins present in coffee silverskin, the only by-product of the roasting process, are formed via the Maillard reaction. The exact structure, biological properties, and mechanism of action of coffee silverskin melanoidins, remain unknown. This research work aimed to contribute to this novel knowledge. To achieve this goal, melanoidins were obtained from an aqueous extract of Arabica coffee silverskin (WO2013004873A1) and was isolated through ultrafiltration (>10 kDa). The isolation protocol was optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 53 publications
2
47
0
Order By: Relevance
“…In addition, an isolated melanoidin fraction (MEL) obtained from CS, mainly composed of dietary fiber (75%) and melanoidins (15%), showed antioxidant capacity in vitro and was effective against induced oxidative stress in rat intestinal cell lines. Furthermore, the fiber effect of this fraction was confirmed in vivo when rats treated with MEL for 28 days showed an acceleration of intestinal transit compared to control animals [ 66 ].…”
Section: Nutritional Value and Health Promoting Propertiesmentioning
confidence: 99%
“…In addition, an isolated melanoidin fraction (MEL) obtained from CS, mainly composed of dietary fiber (75%) and melanoidins (15%), showed antioxidant capacity in vitro and was effective against induced oxidative stress in rat intestinal cell lines. Furthermore, the fiber effect of this fraction was confirmed in vivo when rats treated with MEL for 28 days showed an acceleration of intestinal transit compared to control animals [ 66 ].…”
Section: Nutritional Value and Health Promoting Propertiesmentioning
confidence: 99%
“…The other radiographic study of gastrointestinal motility performed by our group evaluated the effect of melanoidins from the previously mentioned aqueous extract of coffee silverskin [ 178 ]. Coffee silverskin is the tegument of the outer layer of the coffee bean, representing approximately 4.2% (w/w) of the coffee cherry and is the only by-product produced during coffee roasting [ 179 ].…”
Section: Coffee and The Gastrointestinal Tract: Focus On Motor Funmentioning
confidence: 99%
“…Interestingly, fecal pellets from the melanoidin group tended to be slightly larger, which might have been a result of the higher fiber intake in this group, making the fecal pellets slightly more effective to mechanically stimulate the colon. Moreover, melanoidins did not significantly alter the latency of expulsion of a bead inserted 3 cm into the colorectum, suggesting that the motor agents (intrinsic and extrinsic innervation, smooth muscle, and ICCs) involved in the colonic propulsion at this level were not altered by dietary exposure to coffee silverskin-derived melanoidins and that these may have potential to be used as a functional food ingredient [ 178 ]. Interestingly, Argirova et al (2010) [ 185 ] showed that melanoidins act upon muscle tone and might facilitate Ca 2+ influx into the cells of isolated gastric muscle layers.…”
Section: Coffee and The Gastrointestinal Tract: Focus On Motor Funmentioning
confidence: 99%
“…Moreover, according to De La Cruz et al . (2019), during the roasting process phenolic compounds could bind to the initial melanoidin skeleton composed of carbohydrates and proteins. Phenolic compounds are well known because of their strong antioxidant activity, and it is probable that they could act together with the melanoidins in the gastrointestinal tract (Saura‐Calixto, 2011).…”
Section: Resultsmentioning
confidence: 99%